Resource Allocation in Space-Division Multiplexing-Based Elastic Optical Networks - Trindade, Silvana; da Fonseca, Nelson Luis Saldanha (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2020)
This paper presents the work developed in the MSc. thesis entitled ”Resource Allocation in Space-Division Multiplexing-Based Elastic Optical Networks” which explores the resource allocation problem in Space-Division Multiplexing-based Elastic Optical Networks (SDM-EON). The proposed algorithms jointly address spectrum fragmentation, modulation format, crosstalk, and energy consumption. Results demonstrate that our algorithms increase the acceptance of requests for lightpath establishment while handling energy consumption, spectrum fragmentation, energy consumption, load balance, and crosstalk.